Amazonian stingless bees: lethal concentration and mortality after exposure to insecticide in Melipona interrupta Latreire, 1811 (Hymenoptera: Apidae) - Campos, Douglas de; Silva-Lima, Juciane Conceição da; Carvalho-Zilse, Gislene Almeida (EntomoBrasilis, 2024)
Neonicotinoid insecticides can cause a reduction in feeding rate, locomotion, and behavioral changes such as a reduction in flight speed and distance traveled by adult bees. Chronic exposure to sublethal concentrations can result in behavioral disorders and memory loss. This study investigated the effects of insecticides on Amazonian stingless bees, evaluated whether Melipona interrupta Latreire, 1811, is sensitive and does not reject food contaminated with Thiamethoxam, and compared the effects on native stingless bees from the northern region to Apis mellifera. Mortality was evaluated in these bees when exposed to Tiamethoxam (absolute standard AS and Actara 250 WG - commercial product) and Dimethoate AS as a positive control, thus verifying the lethal concentration 50 (LC50) for the species M. interrupta, popularly known as jupará. The mortality of forager workers exposed to active ingredient formulations indicated an LC50 of 24.77 ng/μL for Dimethoate, validating the tests, and 1.28 ng/μL for Tiamethoxam AS and 1.22 ng/μL for Actara 250 WG, values much lower than those found for A. mellifera bees, which were 4.28 ng i.a./µL of Tiamethoxam. Therefore, we concluded that formulations with the active ingredients Dimethoate and Tiamethoxam are highly toxic to Amazonian bees of the species M. interrupta.